Simple Equipment to Reduce Moisture Content in Paddy by Mean of Solar Energy - Techarungpaisan, Pisit; Udomsirichakorn, Kaew; Theerapongthanakorn, Suwat (Engineering and Applied Science Research, 2015)
This paper presents a simple equIpment to reduce moisture content in paddy by mean or solar energy. This is the novel method. The dryer is operated by using solar pond principle. It is a close system which does not allow the air tlow through giving the higher inside air temperature and paddy temperature than that of the conventional system. This will reduce the rate of drying time. The advantages of this instrument are using the local materiaL cheap, easy to rabricate, easy to use; and no energy cost because it uses the solar energy which have high potential available in Thailand. The experimental result shows that it is suitable for drying the paddy and is possible to develop to dry other fruits.